The Tibetan book of the dead for beginners: a guide to living and dying - Lama Lhanang, Rinpoche (Sounds True, 2023)
"Through countless editions and across centuries, the Tibetan Book of the Dead has drawn readers intrigued by the Tibetan Buddhist view of the end of life. In a world that often ignores death or hides it from view, Tibetan Buddhists acknowledge it as the last of a countless series of endings in this lifetime. And after each ending comes a new beginning. The Tibetan Book of the Dead for Beginners draws on this timeless wisdom to help readers today live with more joy and approach the end of life with more ease. Lama Lhanang Rinpoche, born and raised in Tibet and now teaching in the United States and internationally, partners with student and meditation teacher Mordy Levine to share teachings inspired by the Tibetan Book of the Dead. They make clear that "how we live is how we will die." The book explores karma, the end of life, and what happens after death, and it shares accessible practices to cultivate wisdom and compassion along the way. With empathy and warmth, Lama Lhanang and Levine offer support for readers grappling with their own mortality as well as care for loved ones at the end of life. The Tibetan Book of the Dead for Beginners helps readers cultivate courage and embrace the unknown-not just at the end of life, but every day"--